A slotted plus-shaped antenna with a DGS for 5G Sub-6 GHz/WiMAX applications. Issue 12 (December 2022) - Chandra Paul, Liton; Chandra Das, Sajeeb; Rani, Tithi; Muyeen, S.M.; Shezan, Sk. A.; Ishraque, Md. Fatin
Abstract: A slotted plus-shaped patch antenna (PSPA) with defected ground structure (DGS) is modelled and proposed for 5G Sub-6 GHz and WiMAX applications by using computer simulation technology (CST) MWS suite. The PSPA incorporates a rectangular slotted plus-shaped metal patch and a DGS. The PSPA is designed on a Rogers RT5880 (lossy) substrate with a compact dimension of 20 × 35 × 0.79 mm 3 . Its reflection coefficient is -52.06 dB resonating at 3.12 GHz and operates over a wider bandwidth of 2.56 GHz (2.67–5.23 GHz) to accommodate suitable Sub-6 GHz bands. The PSPA has a good gain (2.44 dB), directivity (2.53 dBi), and VSWR (1.005) at 3.12 GHz with omnidirectional radiation characteristics. The maximum efficiency of the proposed PSPA is about 98% for almost loss free power radiation. The apex of estimated gain and directivity are 4.65 dB and 4.95 dBi. The impact of different physical parameters on the antenna performance has also been studied and analysed in this paper. Initially, the proposed PSPA has been investigated by using time domain (TD) solver of CST then again it is buttressed by applying frequency domain (FD) solver of CST. Furthermore, the design has also been verified by high-frequency structure simulator (HFSS) as well as FEKO (a computational electromagnetics software). All the simulators show a very good agreement in results. Highlights: A slotted plus-shaped compact patch antenna is modelled and proposed for 5G Sub-6 GHz/WiMAX Applications. The designed antenna possesses a very low reflection loss (-52.06 dB) and wide bandwidth of 2.56 GHz ranging from 2.67 GHz to 5.23 GHz. The antenna is highly efficient (maximum efficiency is about 98%) with a peak gain of 4.65 dB. The proposed design is validated by both time domain and frequency domain analysis. Abstract : Index Terms—plus-shaped slot; Patch antenna; DGS; 5G; Sub-6 GHz; WiMAX.